EFFECT OF MIXED FEEDING SCHEDULE ON GROWTH AND NUTRIENT UTILISATION IN ROHU, LABEO ROHITA (HAM.) FINGERLINGS - SAMAL, J. K.; MOHANTY, S. N. (Journal of Indian Fisheries Association, 2015)
Studies on nutrient utilisation and growth of rohu (Labeo rohita)fingerlings (3.13-4.09 g) raised on seven feeding schedules underlaboratory conditions (26.3-33.5Â°C) showed that two days regular feedingon Diet B (high protein, 38.90%) resulted in maximum growth andprotein retention efficiency. While regular feeding on low protein diet(Diet .A) resulted in poor nutrient utilisation and growth of fish, highprotein diet (Diet B) did not show any significant difference in growthfrom the mixed 2A-3B schedules but exhibited comparatively lowprotein retention efficiency. The other feeding schedules were 1A-2B,1A-3B, 2A-2B AND 2A-4B, where the numerical value refers to thenumber of days for continuous feeding of a particular diet. The dietsA and B served as the controls which contained 3.40 and 3.67 kcallggross energy respectively.The 2A-3B feeding schedule was also found to be highly economicas an expenditure of Rs.ll/- only was required for raising the bodyweight by one kilo as against Rs.17/- with high protein diet (Diet B) ascalculated.